2018
DOI: 10.1111/papt.12185
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing resilience in adult mental health literature: A systematic review and narrative synthesis

Abstract: When considering and reading about 'resilience', one should be aware that there are different concepts of it. The main difference is between resilience as a personal characteristic and resilience as a process. Therapy may address resilience as a personal characteristic by utilizing individual and social resources. The therapeutic process may be understood as resilience in form of bouncing back and personal growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
103
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 57 publications
1
103
0
1
Order By: Relevance
“…Wachs [79] Li [108] Resilient people have the ability to adjust and cope successfully in the face of adversity, exhibiting a stable trajectory of healthy functioning across time and the capacity for positive emotions after having experienced stressful life events.…”
Section: Reference Articles Definition Proposed Citation Sourcementioning
confidence: 99%
“…Wachs [79] Li [108] Resilient people have the ability to adjust and cope successfully in the face of adversity, exhibiting a stable trajectory of healthy functioning across time and the capacity for positive emotions after having experienced stressful life events.…”
Section: Reference Articles Definition Proposed Citation Sourcementioning
confidence: 99%
“…13 For example, a recent literature review identified resilience as a dynamic process, encompassing immunity, growth and bouncing back, and as a characteristic, including personal and social resources. 14 In relation to the three conceptualisations, the current study defined psychological resilience as outcomes, attributes or processes of coping with, adapting to and rebounding from adverse events. [13][14][15][16] Several studies have examined psychological resilience to suicidal experiences in people with schizophrenia.…”
mentioning
confidence: 99%
“…14 In relation to the three conceptualisations, the current study defined psychological resilience as outcomes, attributes or processes of coping with, adapting to and rebounding from adverse events. [13][14][15][16] Several studies have examined psychological resilience to suicidal experiences in people with schizophrenia. 7,[17][18][19][20] A qualitative study reported a spectrum of psychological factors including passive acceptance, resistance (inner strength, getting on with things, withstanding pressure), and active responses (cognitive and emotional coping strategies) as potentially contributing to psychological resilience.…”
mentioning
confidence: 99%
“…Resilience is a complex construct, increasingly recognized as playing an important role in chronic illness in general and particularly in FMS [ 17 ]. While resilience has been given different definitions over history and in varying scientific disciplines, internal personal characteristics such as balance, perseverance, self-reliance, and, possibly most importantly, attribution of meaning and purpose to life are among the most important attributes of this concept [ 18 , 19 ]. Resilience is associated with important neurophysiological aspects, such as the capacity to perform inhibition of the amygdala by the median prefrontal cortex (mPFC), which can protect against the development of PTSD and chronic pain [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%